Nuclear magnetic resonance methods to characterize lipid-protein interactions at membrane surfaces. - Watts, A (Kluwer Academic Publishers-Plenum Publishers, 1987)
Specific molecular interactions that determine many of the functions of a biomembrane have a high probability of occurring at the surface of that membrane. However, unlike their hydrophobic core, the polar-apolar interface of biomembranes has been somewhat neglected experimentally. Reasons for this are that the chemical heterogeneity encountered makes a simple description difficult and that probing the membrane surface often involves a perturbation of those very interactions being studied. Classical methods for obtaining structural information about biomolecules, including X-ray diffraction, electron microscopy, and more recently high-resolution 2D nuclear magnetic resonance techniques are inappropriate for all but the simplest of membrane problems. In an effort to throw light on how membrane surfaces are organized, both architecturally and dynamically, protons in lipids and proteins have been selectively replaced by deuterons and the resultant deuterium NMR spectrum analyzed to give structural and dynamic information about the molecular associations between a range of membrane components. In principle, lipids, proteins, and oligosaccharides can be studied by this method and the information gained related to biochemical integrity and function. With one or two notable exceptions, the majority of the studies reported so far have been on model systems. A comprehensive review of the literature will not be presented here. However, protein-lipid molecular specificity in membranes, peptide-induced lateral separation, and the ionization behavior of deuterated phospholipids and peripheral proteins will all be demonstrated predominantly using deuterium NMR methods. Some suggestions for future work are also presented.